If you were an adverb - Dahl, Michael; Gray, Sara (Minneapolis, MN : Picture Window Books, 2006)
Simple text and drawings show how adverbs are used to help build sentences.
Includes bibliographical references (p. 24) and index.
2.7
K-3
Keywords: English language -- Adverb -- Juvenile literature; English language -- Adverb; English language -- Parts of speech